Induction chemotherapy followed by radiotherapy versus concurrent chemoradiotherapy in the treatment of different risk locoregionally advanced nasopharyngeal carcinoma. (June 2020) - Liu, Li-Ting; Liang, Yu-Jing; Guo, Shan-Shan; Mo, Hao-Yuan; Guo, Ling; Wen, Yue-Feng; Xie, Hao-Jun; Tang, Qing-Nan; Sun, Xue-Song; Liu, Sai-Lan; Li, Xiao-Yun; Yang, Jin-Hao; et al.
Background: This study aimed to investigate the efficiency and toxicities of concurrent chemoradiotherapy (CCRT) and induction chemotherapy (IC) followed by radiotherapy (RT) in different risk locoregionally advanced nasopharyngeal carcinoma (NPC). Methods: A total of 1814 eligible patients with stage II–IVB disease treated with CCRT or IC plus RT were included. The overall survival (OS), progression-free survival (PFS) and distant metastasis-free survival (DMFS) were calculated using the Kaplan–Meier method, and the differences were compared using the log-rank test. Results: Nomograms were developed to predict OS, PFS and DMFS (C-index: 0.71, 0.70 and 0.71, respectively). Patients were then divided into three different risk groups based on the scores calculated by the nomogram for OS. In the low and intermediate-risk group, no significant survival differences were observed between patients treated with IC plus RT alone and CCRT (5-year OS, 97.3% versus 95.6%, p  = 0.642 and 87.6% versus 89.7%, p  = 0.381, respectively; PFS, 95.9% versus 95.6%, p  = 0.325 and 87.6% versus 89.0%, p  = 0.160, respectively; DMFS, 97.2% versus 94.8%, p  = 0.339 and 87.2% versus 89.3%, p  = 0.628, respectively). However, in the high-risk group, IC plus RT displayed an unfavorable 5-year OS (71.0% versus 77.2%, p  = 0.022) and PFS (69.4.0% versus 75.4%, p  = 0.019) compared with CCRT. A significantly higher incidence of grade 3 and 4 adverse events was documented in patients treated with CCRT than in those treated with IC plus RT in all risk groups ( p  = 0.040). Conclusion: IC followed by RT represents an alternative treatment strategy to CCRT for patients with low and intermediate-risk NPC, but it is not recommended for patients with high-risk NPC.